Impact of COVID-19 Pandemic on Postgraduate Training in Pediatrics - Hamid, Muhammad Haroon; Bilal Mazher; Saamia Aslam; Aiman Shirin; Tayyab Javed (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the impact of the coronavirus disease-2019 pandemic on paediatric postgraduate training as perceived by the trainees. Method: The cross-sectional exploratory study was conducted at the Department of Paediatrics, King Edward Medical University, Lahore, Pakistan, from May to June 2020, and comprised paediatric postgraduate trainees associated with various hospitals across the country who were approached online with a pre-designed 24-item questionnaire during the peak months of the pandemic. Data was analysed using SPSS 25. Results: Of the 226 postgraduates, 134(59.2%) were females. The overall mean age was 28.85±3.06 years. Of the total, 200(88.5%) and 195(86.2%) reported that pandemic had adversely impacted their training and research. The number of trainees managing >30 patients and doing >5 procedures per week before the pandemic decreased from 126(55.8%) and 150(66.4%) to 38(16.8%) and 41(18.1%), respectively, during the pandemic (p=0.01). Regarding e-learning, 168(74.3%) trainees thought it might partly compensate for training, 135(59.7%) showed readiness for it, and 179(79.2%) believed this could not replace actual patient interaction. Conclusion: The coronavirus disease-2019 pandemic was found to have adversely impacted paediatric postgraduate training. Key Words: COVID-19, Paediatrics, Impact, Postgraduate, Training.